Financial Management Behavior of Millennials - Saputra, Fendi (International Journal of Business, Law, and Education, 2024)
Finance is an important aspect of our daily lives. Managing our finances well can help us achieve our financial goals, face financial challenges, and build a more financially stable future. Financial management in the millennial generation is not yet optimal, there are still many problems faced, including high levels of debt, consumer lifestyle, lack of understanding about investment, changes in lifestyle and consumption patterns. This research study uses qualitative methods. This research study involved 3 informants to provide information related to the study carried out. The findings from this research are that the millennial generation has a diverse understanding of financial management, investment and debt management, the millennial generation shows a combination of internal and external locus of control in financial management and the COVID-19 pandemic has brought significant changes in expenditure, income, and the financial habits of the millennial generation. They are more careful in managing their finances, prioritizing important expenses, and strengthening long-term financial preparations.